2020
DOI: 10.1155/2020/2010924
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between SP142 PD-L1 Expression and 18F-FDG Uptake in Non-Small-Cell Lung Cancer

Abstract: Objectives. Immune checkpoint blockers constitute the first-line treatment for advanced non-small-cell lung cancer (NSCLC) with ≥50% PD-L1 expression. In NSCLC, PD-L1 positivity is correlated with high 18F-fluorodeoxyglucose (18F-FDG) uptake. However, these studies only included patients undergoing surgical resection, almost all in their early stages. Moreover, differences in 18F-FDG uptake between NSCLC with high (≥50%) and low (49%) PD-L1 expression remain unknown. We aimed to investigate the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The SUVmax in patients with PD-L1 expression (TPS ≥ 5%) was significantly higher than that without PD-L1 expression in NSCLC [8]. Zhao et al also demonstrated that SUVmax was higher in the high PD-L1 expression group (TPS ≥ 50%) than in the low PD-L1 expression group (TPS: 1-49%) in NSCLC [9]. In contrast, Lopci et al found no significant association between PD-L1 expression level and SUVmax in NSCLC [16].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The SUVmax in patients with PD-L1 expression (TPS ≥ 5%) was significantly higher than that without PD-L1 expression in NSCLC [8]. Zhao et al also demonstrated that SUVmax was higher in the high PD-L1 expression group (TPS ≥ 50%) than in the low PD-L1 expression group (TPS: 1-49%) in NSCLC [9]. In contrast, Lopci et al found no significant association between PD-L1 expression level and SUVmax in NSCLC [16].…”
Section: Discussionmentioning
confidence: 96%
“…PD-L1 TPS <1%, 1-49%, and ≥50% were considered to be negative PD-L1 expression, low PD-L1 expression, and high PD-L1 expression, respectively [9,17]. The patients were divided into six groups based on their EGFR mutation status and PD-L1 expression level, that is, EGFR-mutated and negative PD-L1 expression (EGFR mutant/negative PD-L1), low PD-L1 expression (EGFR mutant/low PD-L1), and high PD-L1 expression (EGFR mutant/high PD-L1), and wild-type EGFR and negative PD-L1 expression (EGFR wild/negative PD-L1), low PD-L1 expression (EGFR wild/low PD-L1), and high PD-L1 expression (EGFR wild/high PD-L1) groups.…”
Section: Epidermal Growth Factor Receptor Mutation Testing Pd-l1 Immu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of researches on the application of 18 F-FDG PET/CT imaging on TIME characterization focused on nonsmall-cell lung cancer (NSCLC) (Table 1). Zhao et al carried out two studies with the largest sample sizes (419 cases and 428 cases) to investigate the relationship between PD-L1 expression and 18 F-FDG uptake, using 22C3 and SP142 assays, respectively (19,20). They both showed that maximum standardized uptake value (SUVmax) was significantly associated with PD-L1 expression in NSCLC.…”
Section: Characterization Of Timementioning
confidence: 99%
“…A metabolic score derived from combined assessment of pretreatment MTV and the neutrophil-to-lymphocyte ratio may provide a more accurate prediction of outcome than either of these factors alone (47,48). Furthermore, in patients with NSCLC, the maximal standard uptake value (SUV) of 18 F-FDG has been reported to be positively associated with PD-L1 expression (49,50), and high 18 F-FDG MTV is associated with PD-L1 expression ≥75% (48). However, 18 F-FDG PET imaging, like computed tomography (CT), can show pseudoprogression (an early increase in tumor volume and FDG uptake on imaging with a subsequent favorable response to ICI therapy) (51,52).…”
Section: Clinical Utility Of Current Pet Tracersmentioning
confidence: 99%